SOLVING THE FUZZY ANTAGONISTIC 2 × 2-GAME - Romanuk, V. V. (Radio Electronics, Computer Science, Control, 2011)
There has been represented a concept of solving the antagonistic 2 × 2-game, whose matrix elements are defined in the form of non-one-element sets. It has been revealed that the solution of such fuzzy game may be a special intersection of solutions of all ordinary 2 × 2-games, whose matrices elements constitute those sets. For cases when such intersection appears to be empty, it is suggested to use a fuzzy solution of a fuzzy 2 × 2- game. If this solution is unacceptable, a noncooperative metagame is constructed, the solution of which will contain the optimal behavior of both players in the initial fuzzy 2 × 2-game.